1997
DOI: 10.1093/ps/76.12.1738
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal glucose uptake and oxygen consumption in turkey poults selected for rapid growth

Abstract: Two lines of turkey poults, one selected for rapid growth at 16 wk of age (F line) and the other a randombred control line (RBC2) were used to investigate the effect of selection for rapid growth on jejunal O2 consumption and glucose transport as well as whole-body O2 consumption. All trials used unsexed poults and were designed as a randomized complete block with day and line as independent variables. In Trial 1, 120 turkey poults, fed a standard starter ration (25.5% CP), were used to examine the effect of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 12 publications
4
69
0
3
Order By: Relevance
“…The changes in small intestinal morphology and in particular the villus height and crypt depth of duodenum, jejunum and ileum are indicative of gut health and digestive capacity of pigs. Increased villus height is directly correlated with an increased epithelial turnover (Fan et al, 1997), and longer villi correlate with the activation of cell mitosis (Samanya and Yamauchi, 2002). In the present study, dietary supplementation with bacteriophages and probiotics (P = 0.053) reported increased villus height of duodenum.…”
Section: Discussionsupporting
confidence: 54%
“…The changes in small intestinal morphology and in particular the villus height and crypt depth of duodenum, jejunum and ileum are indicative of gut health and digestive capacity of pigs. Increased villus height is directly correlated with an increased epithelial turnover (Fan et al, 1997), and longer villi correlate with the activation of cell mitosis (Samanya and Yamauchi, 2002). In the present study, dietary supplementation with bacteriophages and probiotics (P = 0.053) reported increased villus height of duodenum.…”
Section: Discussionsupporting
confidence: 54%
“…In this regard, poor nutrient absorption may occur due to the decrease in villus height and increase in crypt depth. Similarly, Fan et al (1997) reported that the villus height:crypt depth ratio was closely associated with increased epithelial cell turnover. Also, Samanya and Yamauchi (2002) observed that longer villi were correlated with activated cell mitosis in chickens.…”
Section: Discussionmentioning
confidence: 90%
“…Further, an increase in the villus height and villus height to crypt depth ratio are directly correlated with increased epithelial cell turnover (Fan et al, 1997) and an indicator of activated intestinal villi function (Langhout et al, 1999;Shamoto and Yamauchi, 2000) and it also stimulates intestinal blood flow. In addition, butyrate of stimulates cell growth and differentiation of normal cells and apoptosis (early cell death) of tumour cells which represents'butyrate paradox' (Canani et al, 2011).Previous studies showed increased jejunum villi height (Adil et al, 2010;Jerzsele et al, 2012;Chamba et al, 2014), villi height to crypt depth ratio (Hu and Guo, 2007;Shahir et al, 2013) and comparable crypt depth (Hu and Guo, 2007;Adil et al, 2010;Smulikowska et al, 2009;Chamba et al, 2014;Sayrafi et al, 2011;Antongiovanni et al, 2007) by supplementation of different forms of butyric acid.…”
Section: Antioxidant Effectmentioning
confidence: 99%